Surgical margins and oncologic results after carcinoma of the external auditory canal. (25th May 2015) - Ihler, Friedrich; Koopmann, Mario; Weiss, Bernhard G.; Dröge, Leif Hendrik; Durisin, Martin; Christiansen, Hans; Weiß, Daniel; Canis, Martin; Wolff, Hendrik A.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis External auditory canal cancer is rare and carries a poor prognosis. To date, only a few studies provide evidence for clinical decision making in multimodal treatment. Methods Retrospective chart review of 36 cases in three tertiary referral centers. Results Thirteen patients were treated by surgery alone, 18 by surgery with adjuvant chemoradiotherapy (CRT) and five by primary CRT. Clear surgical margins (R0) were obtained in 19 patients and positive margins (R1) in 12. The 5‐year overall survival and local control rates were 59.4% and 74.2% with R0 status versus 56.6% and 26.3% with R1 status. The 5‐year overall survival and local control rates were 46.2% and 70.7% with surgery alone, 78.1% and 43.2% with surgery and adjuvant CRT, and 25.0% and 80.0% with primary CRT. Conclusion Surgery is integral to the management of external auditory canal cancer, whereas CRT is necessary as an adjuvant or primary treatment, depending on tumor stage. Level of Evidence 4. Laryngoscope, 125:2107–2112, 2015